Situation Report: Hungary, 6 March 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Minister of Finance in the United States MTI to Install US-Japanese Video Display Terminals From Minsk: New Proposal to Strengthen Influence of Local Legislators Role and Development of Advertising More Help to Foster Small-Scale Farming Agriculture Facing Steep Hurdles in 1979 Shortage of Pork despite Record Number of Hogs Reaction to the Chinese Invasion of Vietnam